Impact of Design Research on Industrial Practice Tools, Technology, and Training - Chakrabarti, Amaresh; Lindemann, Udo.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Showcasing exemplars of how various aspects of design research were successfully transitioned into and influenced, design practice, this book features chapters written by eminent international researchers and practitioners from industry on the Impact of Design Research on Industrial Practice. Chapters written by internationally acclaimed researchers of design analyse the findings (guidelines, methods and tools), technologies/products and educational approaches that have been transferred as tools, technologies and people to transform industrial practice of engineering design, whilst the chapters that are written by industrial practitioners describe their experience of how various tools, technologies and training impacted design practice. The main benefit of this book, for educators, researchers and practitioners in (engineering) design, will be access to a comprehensive coverage of case studies of successful transfer of outcomes of design research into practice; as well as guidelines and platforms for successful transfer of research into practice.
Preparing for the Transfer of Research Results Into Practice: Best Practice Heuristics -- Are Methods the Key to Product Development Success? An Empirical Analysis of Method Application in New Product Development -- Patterns and Paths for Realising Design-led Impact: A Study of UK REF Cases Studies -- Impacts of Function-Related Research on Education and Industry -- A Framework for the Dissemination of Design Research Focused on Innovation -- Impact of Design Research on Practice: The IISc Experience -- Industrial, and Innovation Design Engineering. Preparing for the Transfer of Research Results Into Practice: Best Practice Heuristics -- Are Methods the Key to Product Development Success? An Empirical Analysis of Method Application in New Product Development -- Patterns and Paths for Realising Design-led Impact: A Study of UK REF Cases Studies -- Impacts of Function-Related Research on Education and Industry -- A Framework for the Dissemination of Design Research Focused on Innovation -- Impact of Design Research on Practice: The IISc Experience -- Industrial, and Innovation Design Engineering. Preparing for the Transfer of Research Results Into Practice: Best Practice Heuristics -- Are Methods the Key to Product Development Success? An Empirical Analysis of Method Application in New Product Development -- Patterns and Paths for Realising Design-led Impact: A Study of UK REF Cases Studies -- Impacts of Function-Related Research on Education and Industry -- A Framework for the Dissemination of Design Research Focused on Innovation -- Impact of Design Research on Practice: The II Sc Experience -- Industrial, and Innovation Design Engineering.
Keywords: Engineering design; Manufactures; Industrial Management; Engineering Design; Machines, Tools, Processes; Industrial Management